School Management in Handling Cases of Problematic Students at Lengayang 3 State Senior High School - Dedi Effendi; Neviyarni N; Yarmis Syukur (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explain how Lengayang 3 State Senior High School manages the management of problem students through a series of activities designed for initial identification, comprehensive assessment, intervention, and ongoing follow-up monitoring. The study used descriptive qualitative methods, using in-depth interviews, school environment observations, and document reviews as the primary data sources. The results indicate that students face various problems such as rule violations, decreased interest in learning, social conflict, and emotional stress influenced by family situations, friendships, and academic burdens. Guidance and counseling teachers handle cases through collaboration with subject teachers and homeroom teachers, followed by in-depth assessments and interventions based on a humanistic approach. Supporting factors include educator collaboration, principal support, and parental involvement. However, the limited number of guidance and counseling teachers, inadequate facilities, and the negative stigma surrounding counseling are major obstacles. These findings emphasize the importance of strengthening guidance and counseling services and improving the professionalism of guidance and counseling teachers.